A rare case of REM sleep-related bradyarrhythmia syndrome with concomitant severe hypertension: a case report and a review of literature - Jakutis, Gabrielius; Juknevičius, Vytautas; Barysienė, Juratė; Matačiūnienė, Dalia; Petrauskienė, Birutė; Petrulionienė, Žaneta; Laucevičius, Aleksandras (Acta medica Lituanica, 2018)
Introduction. Rapid eye movement (REM) sleep-related bradyarrhythmia syndrome is characterized by pathological asystoles during the REM sleep phase. It is a rare rhythm disorder, being reported only few times in the literature. Due to non-specific symptoms, REM sleep-related bradyarrhythmia might be often underdiagnosed. Other cardiac diseases associated with pathological sinus arrests must be excluded to establish the correct diagnosis of and appropriate therapy for REM sleep-related bradyarrhythmia. We report a case of this syndrome followed by hypertension and diastolic heart failure. The case. A 49-year-old male with severe hypertension presented for a cardiologist’s consultation. His main complaints were palpitations, fatigue, dyspnoea, and snoring. Polysomnography test revealed a normal sleep structure with episodes of bradycardia and increased parasympathetic activity during phasic events of REM sleep. Heart rate variability Poincare plot analysis demonstrated similar results. REM sleep-related bradyarrhythmia syndrome was diagnosed and patient was treated with dual chamber heart pacemaker implantation. Discussion. Various components of the autonomic nervous system influence the development of REM sleep-related bradyarrhythmia syndrome. The main factor is likely an increased vagal tone during the phasic REM sleep with the absence of normal compensatory sympathetic activity. Concomitant hypertension in REM sleep-related bradyarrhythmia syndrome is caused by a paradoxically abnormal control of the autonomic nervous system and can be explained through the acetylcholine metabolism pathway. Best suited diagnostic and treatment options for REM sleep-related bradyarrhythmia syndrome are discussed. Conclusions. Patients with REM sleep-related bradyarrhythmia syndrome often present with indistinct symptoms. Polysomnography is an essential diagnostic test for the differential diagnosis of various nocturnal arrhythmias and sleep disorders. Severe hypertension is a common complication of sleep disorders and requires appropriate treatment of the underlying condition. An implantation of a heart pacemaker is the first-choice treatment for patients with REM sleep-related bradyarrhythmia syndrome.
Keywords: rapid eye movement sleep-related bradyarrhythmia syndrome; autonomic nervous system; acetylcholine; hypertension; polysomnography